2005
DOI: 10.1007/s11130-005-5104-5
|View full text |Cite
|
Sign up to set email alerts
|

Modulatory Effect of Fenugreek Seed Mucilage and Spent Turmeric on Intestinal and Renal Disaccharidases in Streptozotocin Induced Diabetic Rats

Abstract: To elucidate the effect of feeding fenugreek seed mucilage and spent turmeric (10%) on disaccharidases activities, the specific activities of intestinal and renal disaccharidases viz., sucrase, maltase and lactase were measured in streptozotocin induced diabetic rats. Specific activities of intestinal disaccharidases were increased significantly during diabetes and amelioration of these activities during diabetes was clearly visible by supplementing fenugreek seed mucilage and spent turmeric in the diet. Howev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(13 citation statements)
references
References 29 publications
0
11
0
2
Order By: Relevance
“…These plants have been used frequently to treat patients suffering from diabetes. Although there are scientific reports about antidiabetic activities of some of these plants especially T. foenum-graecum (Abdel- Barry et al 1997;Bordia et al 1997;Dewi et al 2007;Jelodar et al 2005;Kumar et al 2005;Raju et al 2001;Vats et al 2002;Vijayakumar et al 2005;Xue et al 2007), C. sinensis (Babu et al 2007;Gomes et al 1995;Mackenzie et al 2007;Shoji and Nakashima 2006;Tsuneki et al 2004), U. dioica (Bnouham et al 2003;Farzami et al 2003;Onal et al 2005) and their antihyperglycemic mechanisms, there are no previous studies, at least to our knowledge, on the activity of the plants on a-amylase activity. The a-amylase inhibitory activity varied among the tested plants.…”
Section: Resultsmentioning
confidence: 98%
“…These plants have been used frequently to treat patients suffering from diabetes. Although there are scientific reports about antidiabetic activities of some of these plants especially T. foenum-graecum (Abdel- Barry et al 1997;Bordia et al 1997;Dewi et al 2007;Jelodar et al 2005;Kumar et al 2005;Raju et al 2001;Vats et al 2002;Vijayakumar et al 2005;Xue et al 2007), C. sinensis (Babu et al 2007;Gomes et al 1995;Mackenzie et al 2007;Shoji and Nakashima 2006;Tsuneki et al 2004), U. dioica (Bnouham et al 2003;Farzami et al 2003;Onal et al 2005) and their antihyperglycemic mechanisms, there are no previous studies, at least to our knowledge, on the activity of the plants on a-amylase activity. The a-amylase inhibitory activity varied among the tested plants.…”
Section: Resultsmentioning
confidence: 98%
“…It is a highly viscous polysaccharide. Kumar et al (2005) showed that fenugreek seed mucilage influences intestinal and renal disaccharidases in streptozotocin-induced diabetic rats. Fenugreek galactomannan lowered the concentrations of cholesterol in both liver and blood plasma in rats by decreasing the rate of hepatic cholesterol synthesis (Evans et al, 1992).…”
Section: Discussionmentioning
confidence: 99%
“…They are found in rhizomes, roots and seed endosperm and may act as energy reserves (Franz, 1979); they have a high water holding capacity. The cholesterol lowering effect of flax seed (Lucas et al, 2004) and fenugreek (Kumar et al, 2005) has been attributed to the mucilage present in these materials. It was recently shown that isolated mucilage from fenugreek reduced serum and tissue lipid levels and reduced the synthesis of VLDL by liver cells (Boban et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Spent turmeric is rich in dietary fiber (45%), containing both insoluble fiber (43%) and soluble fiber (2%). In our earlier studies we have shown beneficial effects of spent turmeric on various diabetic parameters [13] and also ameliorated intestinal disaccharidase activities [14]. Beneficial effects on GAGs content and tissue composition of various organs such as liver, lungs, heart and testis of diabetic rats [15] are also reported.…”
Section: Introductionmentioning
confidence: 96%